Biofilm Engineering Approaches for Improving the Performance of Microbial Fuel Cells and Bioelectrochemical Systems - Angelaalincy, Maria Joseph; Navanietha Krishnaraj, Rathinam; Shakambari, Ganeshan; Ashokkumar, Balasubramaniem; Kathiresan, Shanmugam; Varalakshmi, Perumal (Frontiers in Energy Research, 2018)
Microbial fuel cells (MFCs) are emerging as a promising future technology for a wide range of applications in addition to sustainable electricity generation. Electroactive (EA) biofilms produced by microorganisms are the key players in the bioelectrochemical systems involving microorganism mediated electrocatalytic reactions. Therefore, genetically modifying the organism for increased production of EA biofilms and improving the extra electron transfer (EET) mechanisms may attribute to increase in current density of a MFC and an increased COD removal in wastewater treatment plant coupled MFC systems. Extracellular polysaccharides (EPS) produced by the organisms attribute to both biofilm formation and electron transfer. Although cell surface modification, media optimization and operation parameters validation are established as enhancement strategies for a fuel cell performance, engineering the vital genes involved in electroactive biofilm formation is the future hope. Therefore, in this review we critically address the biofilm formation mechanisms in electro active microorganisms, strategies for improving the biofilm formation leading to improved electrocatalytic rates for applications in bioelectrochemical systems.